DESIGN, CONSTRUCTION AND EVALUATION OF MOTORIZED OKRA SLICER (Nigerian Journal of Technology, 2008)
A motorized okra slicer was designed, constructed and tested. It has a capacity of 42.8 kg/hr and efficiency of 95% when compared with the manually operated machine and hand slicing methods. It produces slices of uniform thickness with standard deviation and variance of 0.13 and 0.14, respectively.